Optimal uptake rates for initial treatments for cervical cancer in concordance with guidelines in Australia and Canada: Results from two large cancer facilities. Issue 4 (August 2015) - Kang, Yoon-Jung; O'Connell, Dianne L.; Tan, Jeffrey; Lew, Jie-Bin; Demers, Alain; Lotocki, Robert; Kliewer, Erich V.; Hacker, Neville F.; Jackson, Michael; Delaney, Geoff P.; Barton, Michael; Canfell, Karen
Highlights We estimated optimal rates for all initial treatment modalities for cervical cancer. We compared the optimal and the observed rates in Australia and Canada. The overall optimal treatment rates are largely dependent on the stage distribution. Observed surgery rates were similar to the estimated optimal rates. Observed radiotherapy, chemotherapy and chemo-radiotherapy were under-utilised.